Landscape and temporal influences on the winter diet of a threatened diurnal raptor, the Hen Harrier Circus cyaneus. Issue 3 (3rd July 2021) - McCarthy, Alan; Smiddy, Pat; Nagle, Tony; Mee, Allan; Irwin, Sandra; Caravaggi, Anthony; O'Halloran, John
ABSTRACT: Capsule: Habitat composition plays a key role in determining the winter diet of the Hen Harrier Circus cyaneus, which varies across the winter season and between years. Aims: To determine the winter diet of the Hen Harrier and examine temporal and spatial variations in diet composition. Methods: A total of 1117 Hen Harrier pellets were collected from 11 winter roosts between 2017 and 2021 in Ireland. Results: Hen Harrier winter diet was dominated by avian prey (95.9% of pellets), with mammalian prey found in 12.0% of pellets. The occurrence of small birds and small mammals in the diet was positively associated with the proportion of arable, wild bird cover, and low-intensity agriculture around the roost sites. The frequency of medium-sized birds (primarily Redwing Turdus iliacus and Common Snipe Gallinago gallinago ) in the diet was positively associated with the proportion of bog and young conifer forests surrounding roost sites. Diet varied across regions, with pellets from roosts in lowland coastal areas having a greater prevalence of small birds and small mammals, and pellets from roosts in upland areas having a greater prevalence of medium-sized birds. The proportion of medium-sized birds in the diet changed across months, with that of small birds and small mammals remaining stable. There was also variation between winters in the proportion of small- and medium-sized birds in the diet. Conclusions: Habitat, along with region and time, are important drivers of variation in Hen Harrier diet. Our findings highlight the opportunity for the enhancement of Hen Harrier habitat through land management, and can be used to inform effective conservation strategies for wintering Hen Harriers at a landscape scale.